Development of a fortified drink from the mixture of small colombian native fruits (2018)
Strawberry (Fragaria ananassa), blackberry (Rubus glaucus), Peruvian cherry (Physalis peruviana L.) and purple passion fruit (Passiflora edulis Sims) are important fruit crops in Colombia, due to their organoleptic properties and nutritional qualities, making them attractive for international markets. This study was undertaken to characterize the physicochemical properties of these four fruits and to present an alternative for their use. To achieve this goal, the moisture, pH, soluble solids, acidity, color, iron and vitamin C concentration were determined, and a fortified mixed fruit drink was developed. All of the fruits can be classified as high acidity products due to the acidity results. Purple passion fruit and Peruvian cherry presented the highest content of soluble solids, while blackberry, purple passion fruit and Peruvian cherry did not exhibit statistically significant differences in their iron contents, and strawberry exhibited the highest contribution of vitamin C.